DIGITAL TRANSFORMATION IN ISLAMIC EDUCATION: ACHIEVING EQUITABLE ACCESS THROUGH DIGITAL INCLUSION IN THE ERA OF DISRUPTION - Sindy Karulita; Muthia Umi Setyoningrum (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
In today’s world of technological advancements and changes in teaching methods, digital transformation in Islamic education is becoming increasingly important in this disruptive era. This study examines how digitalization can be used to improve access to Islamic education through digital knowledge. The main focus is on the integration of information technology into the educational process, the development of digital skills for students, and the use of intuition to empower marginalized communities. This study uses a qualitative approach with literature review and policy analysis as its primary methodology. The study findings suggest that digital transformation can improve access, raise educational standards, and strengthen the reach of Islamic education worldwide. For this transformation to be successful, collaboration between governments, educational institutions, and the general public is needed to create a healthy and stable digital ecosystem.